2018
DOI: 10.1111/1911-3846.12413
|View full text |Cite
|
Sign up to set email alerts
|

Do Analysts Matter for Corporate Tax Planning? Evidence from a Natural Experiment

Abstract: We exploit an exogenous shock to analyst coverage as a result of brokerage house mergers and closures to examine whether financial analysts influence the tax‐planning activities of the firms they cover. Using a difference‐in‐differences design, we find that, on average, firms affected by broker mergers and/or closures experience a reduction in their GAAP (cash) effective tax rates (ETR) of 2.5 percent (2.6 percent), relative to control firms, translating into average tax expense (cash tax) savings of $34 ($35)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(25 citation statements)
references
References 103 publications
(211 reference statements)
0
25
0
Order By: Relevance
“…Chen, Chiu, and Shevlin [2014] show that tax avoidance increases following declines in analyst coverage associated with broker closures and mergers.…”
Section: Consistent Withmentioning
confidence: 97%
“…Chen, Chiu, and Shevlin [2014] show that tax avoidance increases following declines in analyst coverage associated with broker closures and mergers.…”
Section: Consistent Withmentioning
confidence: 97%
“…An indirect mechanism needs to satisfy two conditions: it can affect tax avoidance and itself is affected by quasi-indexer ownership. For the first condition, prior research has shown that certain aspects of managerial incentives, corporate governance, and information environment are associated with tax avoidance (e.g., Rego and Wilson, 2012;McGuire, Wang, and Wilson, 2014;Chen, Chiu, and Shevlin, 2017). For the second condition, prior studies have shown that quasi-indexer ownership has a causal influence on certain aspects of corporate governance (Appel et al, 2016a;Schmidt and Fahlenbrach, 2017) and firm disclosure and information environment (e.g., Boone and White, 2015), and it is conceivable that they may also affect firms' executive equity incentives.…”
Section: Background and Predictionmentioning
confidence: 99%
“…and White, 2015; Appel et al, 2016a), the impacts of corporate governance and transparency on tax avoidance are ambiguous (e.g., Minnick and Noga, 2010;Robinson, Xue, and Zhang, 2012;Chen and Lin, 2017;Chen, Chiu, and Shevlin, 2017). Given the ambiguous nature of these indirect mechanisms, we treat their effects as open empirical questions and provide detailed analyses in Section 6.…”
Section: Background and Predictionmentioning
confidence: 99%
“…Not only has there been a proliferation of tax‐avoidance measures, there has been an explosion in papers examining the determinants of cross‐sectional and inter‐temporal variation in firms’ tax avoidance. A less‐than‐exhaustive list includes tax avoidance by family firms (Chen, Chen, Cheng, and Shevlin ), the role of executive compensation (Phillips ; Armstrong, Blouin, and Larcker ; Robinson, Sikes, and Weaver ; Rego and Wilson ), the role of institutional ownership (Khurana and Moser ), index institutional investors (Bird and Karolyi ), private equity ownership (Badertscher, Katz, and Rego ) and board characteristics or other governance characteristics such as the G or E index motivated by the agency cost/monitoring story in Desai and Dharmapala (, ) (Armstrong, Blouin, Jagolinzer, and Larcker ), dual‐class ownership (McGuire, Wang, and Wilson ), gender of top management (Francis, Hasan, Wu, and Yan ), analyst coverage (Chen, Chiu, and Shevlin ), the role of foreign operations of U.S. multinationals (Rego ), existence of subsidiaries in tax havens (Dyreng and Lindsey ), the role of Delaware as a domestic tax haven (Dyreng, Lindsey, and Thornock ), managerial fixed effects (Dyreng, Hanlon, and Maydew ), military background of the CEO (Law and Mills ), managerial ability (Koester, Shevlin, and Wangerin ), CEO narcissism (Olsen and Stekelberg ), CEO overconfidence (Chyz, Gaertner, Kausar, and Watson ), CEO personal tax aggressiveness (Chyz ), religiosity of the region of the corporate headquarters (McGuire, Omer, and Sharp ; Boone, Khurana, and Raman ), labor unions (Chyz, Leung, Li, and Rui ), firms’ business strategy (Higgins, Omer, and Phillips ), the auditor as tax service provider (Cook and Omer ; McGuire, Omer, and Wang ), corporate social responsibility (Hoi, Wu, and Zhang ; Watson ), the role of financial constraints (Edwards, Schwab, and Shevlin ), reputation, media and litigation concerns (Graham et al. ), regulatory scrutiny (Kubick, Lynch, Mayberry, and Omer ), government contracting concerns (Mills, Nutter, and Schwab ), IRS audit probabilities (Hoopes, Mescal, and Pittman ), political lobbying (Alexander, Scholz, and Mazza ; Chen, Gunny, and Ramanna ; Barrick and Alexander ; Chen, Dyreng, and Li…”
Section: Overview Of Accounting Tax Literaturementioning
confidence: 99%